Concentric annular heat pipe characterisation analysis for a drying application. (25th February 2019) - Mustaffar, Ahmad; Phan, Anh N.; Reay, David; Boodhoo, Kamelia
Highlights: A new configuration of concentric annular heat pipes was characterised. The entire inner space of the central tube was the condenser for ceramic drying, via screw conveyance. 11% filling ratio was optimum, giving sufficient fluid inventory for wick saturation. Excellent isothermal conditions were achieved: 0.4–1.3 K. Excellent global thermal resistances were achieved: 0.08–0.31 K/W. At 302 W heat input, ceramic moisture was reduced from 33 to 21 wt% within 35 s. Abstract: We present a new configuration of concentric annular heat pipe (CAHP). A CAHP consists of two concentric tubes, with the smaller diameter tube positioned inside the larger one so that an annular space is created by sealing the ends whilst the inner space of the smaller tube is open to the surroundings. Evaporation and condensation take place along the length of the annular space. Unique to our CAHP design, the entire inner space of the central tube was designated as the condenser where wet ceramic slurries were to be conveyed through for moisture reduction. A 515 mm-long stainless steel CAHP was constructed for the present study with 76.2 and 38.1 mm outer and inner tube diameters, respectively. A screen wick was attached only to the inner wall of the outer tube. Several experimental parameters were investigated for their effects on axial temperature profile and thermal resistance: 11–43% filling ratios (a measure of fluid inventory inside the annular space), 0–90° angular orientations and 272–302 W heat inputs. An 11% filling ratio was found to be optimum, giving sufficient fluid inventory for wick saturation and compatible with all orientations and heat inputs. For the 11% filling ratio, vapour temperature differentials between heat pipe extremities were 0.4–1.3 K, showing an excellent isothermal condition. Global thermal resistances were calculated to be 0.08–0.31 K/W. As the wet loads were conveyed through the inner tube, vapour was condensed all along the outside surface of the inner tube, releasing thermal energy to the loads through radial heat transfer. The moisture content of the ceramic slurries was reduced from 33 wt% to 21 wt%, at the highest CAHP heat input of 302 W within 35 s residence time, demonstrating the promising potential of the CAHP as an efficient moisture removal technology.